Recent Development in Carbon-LiFePO4 Cathodes for Lithium-Ion Batteries: A Mini Review - Brindha Ramasubramanian; Subramanian Sundarrajan; Vijila Chellappan; M. V. Reddy; Seeram Ramakrishna; Karim Zaghib (Batteries, 2022)
Li-ion batteries are in demand due to technological advancements in the electronics industry; thus, expanding the battery supply chain and improving its electrochemical performance is crucial. Carbon materials are used to increase the cyclic stability and specific capacity of cathode materials, which are essential to batteries. LiFePO4 (LFP) cathodes are generally safe and have a long cycle life. However, the common LFP cathode has a low inherent conductivity, and adding a carbon nanomaterial significantly influences how well it performs electrochemically. Therefore, the major focus of this review is on the importance, current developments, and future possibilities of carbon-LFP (C-LFP) cathodes in LIBs. Recent research on the impacts of different carbon sizes, LFP’s shape, diffusion, bonding, additives, dopants, and surface functionalization was reviewed. Overall, with suitable modifications, C-LFP cathodes are expected to bring many benefits to the energy storage sector in the forthcoming years.